Evaluation of the PPAR-γ agonist pioglitazone in mild asthma: a double-blind randomized controlled trial - Anderson, J.R.; Mortimer, K.; Pang, Linhua; Smith, K.M.; Bailey, H.; Hodgson, D.B.; Shaw, Dominick E.; Knox, Alan J.; Harrison, Timothy W. (Public Library of Science, 2016)
Background